2019
DOI: 10.1038/s41598-019-50619-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the interaction of hemorphin and its targets

Abstract: Hemorphins are atypical endogenous opioid peptides produced by the cleavage of hemoglobin beta chain. Several studies have reported the therapeutic potential of hemorphin in memory enhancement, blood regulation, and analgesia. However, the mode of interaction of hemorphin with its target remains largely elusive. The decapeptide LVV-hemorphin-7 is the most stable form of hemorphin. It binds with high affinity to mu-opioid receptors (MOR), angiotensin-converting enzyme (ACE) and insulin-regulated aminopeptidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 84 publications
0
16
0
1
Order By: Relevance
“…A number of studies have highlighted their therapeutic potential [10,[17][18][19]47,48]. We had previously reported the molecular binding behavior of camel and non-camel LVV-hemorphin-7 on multiple targets [20,25]. Here, we report the binding and ACE inhibition potential of non-camel hemorphins (LVVYPWTQRF and YPWTQRF) and camel hemorphins (LVVYPWTRRF and YPWTRRF) using computational approaches and an in vitro ACE inhibition assay.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A number of studies have highlighted their therapeutic potential [10,[17][18][19]47,48]. We had previously reported the molecular binding behavior of camel and non-camel LVV-hemorphin-7 on multiple targets [20,25]. Here, we report the binding and ACE inhibition potential of non-camel hemorphins (LVVYPWTQRF and YPWTQRF) and camel hemorphins (LVVYPWTRRF and YPWTRRF) using computational approaches and an in vitro ACE inhibition assay.…”
Section: Discussionmentioning
confidence: 95%
“…The sequence of hemorphin peptide is highly conserved in mammals, which suggests similar biological activities in different mammals under different conditions. However, the camel hemorphin (LVVYPWTRRF) harbors a Q>R variation [25]. Camels have unique genetic adaptations that permit it to survive severe dehydration and very harsh environmental conditions [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Other recent works on the identification of natural peptides are mentioned here: Ali et al [26] investigated the most likely binding poses of the decapeptide LVV-hemorphin-7 (which is the most stable form of hemorphin) with three biological targets, including ACE. They studied mammalian and camel LVV-hemorphin-7 and used computational methods (including docking and MM/GBSA) to calculate the binding affinities, and MD to gain a better understanding of the dynamics of the molecular interactions between the selected targets and hemorphin peptides.…”
Section: Molecular Modeling Applied To the Study Of Ace Inhibitors Inmentioning
confidence: 99%
“…Ali et al presented computational methods to elucidate the alignment of mammalian LVV-H7 to mu-opioid receptors (MOR), angiotensin-converting enzyme (ACE) and insulinregulated aminopeptidase (IRAP) that are its binding counterparts, and to calculate the binding affinity to these proteins [55]. It was shown that camel LVV-H7 produced stronger interactions with all studied proteins (MOR, ACE and IRAP) than non-camel LVV-H7.…”
Section: Other Techniquesmentioning
confidence: 99%